2012
DOI: 10.1017/s0033291712000384
|View full text |Cite
|
Sign up to set email alerts
|

The influence of prior expectations on facial expression discrimination in schizophrenia

Abstract: Overall, the present data suggest an overdependence on prior expectations for threatening stimuli, reflecting belief inflexibility, in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Previous studies have found that prior expectations facilitate perception of emotions, presented in static images, by improving speed and accuracy to discriminate emotions congruent with prior expectations (Barbalat et al, 2013;Barbalat et al, 2012). In the current work, I explored the influence of prior expectations during naturalistic emotion perception, using dynamic, audio-visual videos displaying anger, happy and neutral expressions.…”
Section: Contributions To the Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have found that prior expectations facilitate perception of emotions, presented in static images, by improving speed and accuracy to discriminate emotions congruent with prior expectations (Barbalat et al, 2013;Barbalat et al, 2012). In the current work, I explored the influence of prior expectations during naturalistic emotion perception, using dynamic, audio-visual videos displaying anger, happy and neutral expressions.…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…However, there are some inconsistencies in the prior expectancy literature regarding the nature of aberrancy in SCZ. For example, a study by Barbalat et al (2012) examined the influence that prior expectations have on emotion perception. In their paradigm, expectations were induced by using cues to instruct participants to identify a specific emotion in a sequence of static emotional faces.…”
Section: Prior Expectationsmentioning
confidence: 99%
See 3 more Smart Citations